ANALYSIS OF THE ORGANIZATION OF INTERMODAL TERMINALS IN THE INTERACTION OF GROUND TRANSPORT TYPES - Yakupbaev Khamid Maratovich, Mukhamedova Ziyoda Gafurdjanovna, Boboev Diyor Shomurotovich Tashkent State Transport University (Tashkent, Uzbekistan) (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
The article examines the stages of development of intermodal transports, its current state, and the analysis of research work on the development of innovative terminals. To date, scientists and leading research institutes in domestic and foreign countries have been cited for the organization of intermodal and contrail terminals. In addition, when reloading intermodal transport units from one type of transport to another, the existing problems in the terminals were studied and proposals and recommendations were made to eliminate them.